Exploring Adsorption Performance of Functionalized Mesoporous Silicas with a Different Pore Structure as Strong Cation-Exchange Sorbents for Solid-Phase Extraction of Atropine and Scopolamine - Fernando L. Vera-Baquero; Sonia Morante-Zarcero; Damián Pérez-Quintanilla; Isabel Sierra (Applied Sciences)
In this work, mesoporous silicas with two types of mesoporous structures were synthesized and functionalized with sulfonic acid groups: MCM-41-SO3H (honeycomb-like hexagonal structure) and MSU-2-SO3H (three-dimensional porous structure with wormhole pores). The synthesized materials were characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, nitrogen adsorption–desorption, Fourier-transform infrared spectroscopy, 29Si solid-state nuclear magnetic resonance spectroscopy, and elemental analysis. The obtained functionalized materials were evaluated as sorbents for strong cation-exchange solid-phase extraction (SPE) to determine their efficiency in the adsorption and desorption of tropane alkaloids (atropine and scopolamine). The loading solvents, loading volume, analyte concentration, and elution volume were studied, using 50 mg of both materials. Analyses were carried out by ultra-high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry. The synthesized MCM-41-SO3H material presented the highest recovery efficiency and has proven to be a promising sorbent for strong cation-exchange SPE of atropine and scopolamine in aqueous media. The high degree of functionalization of MCM-41-SO3H and the high accessibility of the sulfonic groups for the target analytes, due to the regularity and uniformity of their pores, maximize the contact between the alkaloids and the sorbent, favoring efficient adsorption.